E-cigarette use and susceptibility among Indonesian youth: the role of social environment, social media, and individual factors - Mouhamad Bigwanto; Melinda Pénzes; Nurul Kodriati; Emma Rachmawati; Nida Amalia; Róbert Urbán (BMC Public Health)
Abstract Background Youth behavior is significantly influenced by their social environment and social media (SM). Susceptibility to e-cigarette use, defined as the likelihood of initiating e-cigarette use among non-users, is a critical early marker for prevention efforts. This study explores the interplay of social environment, SM marketing exposure, and individual traits in e-cigarette use and susceptibility among Indonesian youth, addressing a gap in non-Western contexts. Methods A school-based online survey of 1,600 Indonesian youth aged 15–24, conducted from March to August 2023 in Jakarta, Yogyakarta and East Kalimantan, assessed e-cigarette use, susceptibility, and predictors, including social environment, SM marketing exposure, and sensation-seeking behavior. Structural equation modeling and multinomial regression were used to analyze associations. Results Approximately 13.3% of students reported using e-cigarettes in the past 30 days, and 6.7–10.1% of non-users were susceptible to experimenting with e-cigarettes. Boys were significantly more likely than girls to be current (OR = 6.67, 95% CI [3.05–14.57]) and ever e-cigarette users (OR = 2.92, 95% CI [2.10–4.06]). Sensation-seeking (OR = 2.19, 95% CI [1.83–2.62]), e-cigarette use by horizontal family member (OR = 1.39, 95% CI [1.10–1.53]), number of friends using e-cigarettes (OR = 1.20, 95% CI [1.17–1.23]), and exposure to e-cigarette advertisements on Instagram and TikTok (OR = 1.35, 95% CI [1.20–1.53]) were significant predictors of current use. Among non-users, boys reported higher susceptibility to e-cigarette use than girls (β = 0.20, p <.01). Sensation seeking (β = 0.24, p <.01) and the number of friends using e-cigarettes (β = 0.22, p <.01) were directly associated with susceptibility. Sex-specific patterns were observed: maternal and sisters’ e-cigarette use were associated with increased susceptibility among girls (r =.11, p =.002; r =.17, p <.001), while grandfathers’ use was linked to higher susceptibility among boys (r =.21, p <.001). Notably, TikTok exposure was uniquely associated with greater susceptibility among girls (r =.08, p =.023). Conclusions SM, peers, and family significantly shape youth e-cigarette-related behavior. These findings underscore the need for targeted interventions, including banning e-cigarette advertising on SM, promoting peer-driven prevention strategies, and leveraging SM for educational campaigns to reduce youth e-cigarette use.